(For the aesthetic and dramatic function of Remake films and series) (Journal of the College of Basic Education, 2024)
This research deals with the most important element of the structural and dramatic elements, which is repeating the story that has been processed and transformed into a cinematic or television work. The danger of repeating the work lies in identifying the aspects of previous treatments and directorial solutions and treating them with credibility and realism when presented in the final work for the recipient. The research deals with the research problem that the researcher arrived at with the following question:: What are the treatments for employing aesthetics and drama in Remake films and series? And then the importance of the research, the goal of the research, the limits of the research, and defining the terms), The researcher divided the theoretical framework into two sections, the first was: the role of the elements of the language of the medium in the production of Remake films. The researcher touched on the most important elements of the medium and working with the rest of the elements of the dramatic B, especially the story, and re-processing it again. As for the second section: Remake films and series, this section deals with the most important international, fantasy and imaginative stories and novels that were re-processed again in the Remake production.And then the research procedures, which were divided into (research method, research population, research sample, research tool, analysis unit). As for the fourth chapter, which bears the title (sample analysis), the researcher decided to choose a purposive sample in order to suit it with the requirements of the limits and community of the research. The movie (The Lion King), produced (2019) (directed by Jon Favreau), and the researcher reached the following results:Digital technologies have an essential role in manufacturing and controlling the actions and reactions of characters in Remake films.Fantasy and imaginative stories cannot be implemented realistically and believably without the intervention of digital computer programs.3. Scenes, decorations, accessories, and spaces have an aesthetic and semantic role for Remake films.